Undergraduate Students’ Perceived Stress Levels in Summer Term 2020 – A Comparison to Preceding Academic Terms - Goppert, Simone Antje; Pfost, Maximilian (Frontiers in Psychology, 2021)
The COVID-19 pandemic tremendously affected teaching and learning in both schools and higher education settings. In Germany, university students had to shift from in-person group learning in lectures and seminars to new forms of e-learning and distance teaching. Even before COVID-19, stress was a common experience among university students, and these changes have reinforced students’ stress levels. Based on a sample of n = 110 German university students, this study explores whether students’ perceived stress levels in summer term 2020 differed from their perceived stress levels in preceding academic terms. The results show that students experienced lower levels of stress and higher levels of joy in summer term 2020 compared to preceding academic terms. Despite limitations in the interpretation of these findings, possible explanations such as changes in academic and non-academic workload or decreased demands in university exams are discussed.